Projected filter trust region methods for a semismooth least squares formulation of mixed complementarity problems - Kanzow, Christian; Petra, Stefania (Optimization methods & software, 2008)
A reformulation of the mixed complementarity problem as a box constrained overdetermined system of semismooth equations or, equivalently, a box constrained nonlinear least squares problem with zero residual is presented. On the basis of this reformulation, a trust region method for the solution of mixed complementarity problems is considered. This trust region method contains elements from different areas: a projected Levenberg-Marquardt step in order to guarantee local fast convergence under suitable assumptions, affine scaling matrices which are used to improve the global convergence properties, and a multidimensional filter technique to accept a full step more frequently. Global convergence results as well as local superlinear/quadratic convergence is shown under appropriate assumptions. Moreover, numerical results for the MCPLIB indicate that the overall method is quite robust.